JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT MEDIATING WORKPLACE SPIRITUALITY ON JOB PERFORMANCE - Dwi Wahyu Pril Ranto; Noor Arifin; Purnama Andri Murdapa (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
The aim of this research is to elaborate the role of workplace spirituality in increasing job satisfaction, organizational commitment and organizational performance. The population in this study were lecturers and educational staff at the Nahdlatul Ulama Islamic University Jepara. Convenience sampling was used in this research due to considerations of ease in reaching respondents and efficiency of time used in sampling. Research data was obtained through distributing questionnaires to lecturers and education staff. The data obtained were 88 respondents. To test the hypothesis, Structural Equation Modeling was used and Partial Least Square version 3.0. The research results show that workplace spirituality and organizational commitment have no effect on job performance. However, job satisfaction can improve job performance. The results of this research show that employees who are committed to the organization and happy as a form of representation of workplace spirituality do not make them try to improve their performance. However, satisfied employees are able to contribute to improving organizational performance. And organizational commitment mediates the influence of workplace spirituality on job performance, while job satisfaction does not mediate the influence of workplace spirituality on job performance.